Social skills training for children and adolescents with autism spectrum disorder: a randomized controlled trial - Choque-Olsson, Nora; Bölte, Sven (Journal of the American Academy of Child and Adolescent Psychiatry, 2017)
Objective: Social skills group training (SSGT) for children and adolescents with autism spectrum disorder (ASD) is widely applied, but effectiveness in real-world practice has not yet been properly evaluated. This study sought to bridge this gap. Method: This 12-week pragmatic randomized controlled trial of SSGT compared to standard care alone was conducted at 13 child and adolescent psychiatry outpatient units in Sweden. Twelve sessions of manualized SSGT (“KONTAKT”) were delivered by regular clinical staff. Participants (N = 296; 88 females and 208 males) were children (n = 172) and adolescents (n = 124) aged 8 to 17 years with ASD without intellectual disability. The primary outcome was the Social Responsiveness Scale rating by parents and blinded teachers. Secondary outcomes included parent- and teacher-rated adaptive behaviors, trainer-rated global functioning and clinical severity, and self-reported child and caregiver stress. Assessments were made at baseline, posttreatment, and 3-month follow-up. Moderator analyses were conducted for age and gender. Results: Significant treatment effects on the primary outcome were limited to parent ratings for the adolescent subgroup (posttreatment: -8.3; 95% CI = -14.2 to -1.9; p = .012, effect size [ES] = 0.32; follow-up: -8.6; 95% CI = -15.4 to -1.8; p = .015, ES = 0.33) and females (posttreatment: -8.9; 95% CI = -16.2 to -1.6; p = .019, ES = 0.40). Secondary outcomes indicated moderate effects on adaptive functioning and clinical severity. Conclusion: SSGT for children and adolescents with ASD in regular mental health services is feasible and safe. However, the modest and inconsistent effects underscore the importance of continued efforts to improve SSGT beyond current standards.
Gesehen am 30.10.2018